1044 Evaluating Mode of Delivery of Iron or Iron and Zinc On Iron Status and Iron Stress Markers. (October 2012) - Dhingra, U; Pradhan, A; Menon, VP; Dutta, A; Dhingra, P; Black, R; Madhesiya, S; Gupta, S; Sazawal, S
Abstract : Background: Iron deficiency remains a major nutritional problem among infants and young children in India. The tablet/syrup-based programs do have logistic, supply and compliance challenges. Tablet/Syrup may have increased risk of free iron in blood, oxidative stress and risk of infections. Objective: In a community based RCT we evaluated 3 approaches of iron delivery for impact on iron status, pro and anti-inflammatory interleukins and non-transferrin bound iron (NTBI) with 30 day intervention. Methods: 300 children 22–34 months were enrolled and randomized to receive either iron fortified biscuit (n=74), iron tablet (n=77), iron+ zinc tablet (n=74) or placebo (n=75) for 30 days. Results: Delivery of iron through biscuit showed better impact on hemoglobin (Mean Diff: 0.60; 95 % CI: 0.16–1.04) and other hematological markers like RDW, MCV and MCH at 30 day post supplementation. The NTBI estimation at day 1 and 30 post supplementation, 3 hours after ingestion of supplement dose; an indicator of oxidative stress caused by dose after iron status repletion, suggested the lowest burden with biscuit (2 %) and a higher burden with supplements (6–7 %). At day 30 there was no effect on interleukins in the biscuit group; increase in IL-6/IL10 in iron tablet, increase in IL-8/IL10 in iron+zinc tablet group. Conclusion: Providing iron through fortified biscuits was as efficient and effective in improvement of iron status and hematological markers as iron tablets. Biscuit was marginally better for NTBI or immune response. The benefit of using biscuits needs to be evaluated in a larger community based effectiveness program.